Pelatihan Menulis Kreatif Berbasis Media Populer Pada Alumni Sastra Indonesia di Lingkungan Universitas Pamulang - Rai Bagus Triadi; Natalia Endah Hapsari; Misbah Priagung Nursalim (Jurnal Pengabdian Masyarakat, 2022)
As an educational institution, Indonesian Literature Study Program, Pamulang University is a study program that has good integrity in the South Tangerang City area. This is in accordance with the ranking of the percentage of Indonesian literature alumni users, both in government and non-government. Based on this background, the Indonesian Literature Study Program is committed to producing superior graduates who are ready to compete, therefore it is necessary to have special abilities or competencies that are mastered by alumni according to the characteristics of the Indonesian Literature Study Program, Pamulang University. One of the competencies expected is to be able to write fiction and scientific works. In connection with this commitment, the implementation of the tridarma of community service colleges this semester has the theme of creative writing based on popular media for Indonesian literature alumni at Pamulang University. In this writing training, the alumni were reminded again about writing techniques and the structure of creative writing texts. The speakers in this training are writers in popular media who have very qualified competencies, therefore the participants gain experience to practice directly editing and submitting manuscripts for publication. It is hoped that this training will be useful in the aspect of strengthening the competence of alumni in creative writing skills based on popular media.